Geological field survey in the regions of L*tzow-Holm Bay, Prince Olav Coast and Enderby Land, 2018-2019 (JARE-60) - Toyoshima, Tsuyoshi; Ishikawa, Masahiro; Kitano, Ippei; Katori, Takuma; Hokada, Tomokazu (2019)
The Tenth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Wed. 4 Dec. / 3F Seminar room, National Institute of Polar Research conference object